Unresectable intrahepatic cholangiocarcinoma: TARE or TACE, which one to choose? - Cocozza, Maria Adriana; Braccischi, Lorenzo; De Cinque, Antonio; Bruno, Antonio; Cappelli, Alberta; Renzulli, Matteo; Basile, Antonello; Venturini, Massimo; Lucatelli, Pierleone; Modestino, Francesco; Mosconi, Cristina (Frontiers in Gastroenterology, 2023)
Intrahepatic cholangiocarcinoma (ICC) is the second most common primary liver malignancy and its incidence is rising in Western countries. Although surgical resection is considered the only curative treatment, up to 70% of patients are diagnosed at an advanced stage, which precludes surgical intervention. Those who are inoperable become candidates for systemic treatment. Currently, the combination of gemcitabine and cisplatin is the first-line chemotherapy, with a median overall survival (OS) of about one year. Recently, there has been a notable increase in evidence regarding chemotherapy for biliary tract cancer; however, the effectiveness of the new chemotherapy drugs still needs to be evaluated. Today, intra-arterial therapies (IAT), especially trans-arterial chemoembolization (TACE) and trans-arterial radioembolization (TARE), are widely used. Both TACE and TARE have demonstrated good efficacy in controlling localized disease and in improving survival. However, current literature does not conclusively show whether TACE is superior to TARE 2 This is a provisional file, not the final typeset article or vice versa. As recent meta-analyses have indicated, both TACE and TARE offer suboptimal objective response rates but yield similar positive outcomes. It's important to note that these findings are based on single-center studies, which often include a small number of patients and lack a comparative design. Therefore, when comparing such studies, there's an inevitable selection bias among the treatment groups (TACE or TARE) and significant heterogeneity. This review outlines the current evidence on the use of interventional IAT in managing ICC.